1986
DOI: 10.1177/109019818601300407
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Use During Sexual Activity and Compliance with Safe Sex Guidelines for AIDS: The AIDS Behavioral Research Project

Abstract: This article describes the association between drug and alcohol use during sexual activity and high-risk sex for AIDS. Data to test this association are drawn from a prospective study of the behavioral changes made by gay men in San Francisco in response to the AIDS epidemic. Findings drawn from the May, 1984 and May 1985 waves of data collection are described. The cross-sectional analysis showed that use of particular drugs during sex, the number of drugs used during such activity, and the frequency of combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
165
3

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(175 citation statements)
references
References 9 publications
7
165
3
Order By: Relevance
“…This finding is consistent with research that showed a causal link between illicit drug use and HIV-risk behavior in this population (Halkitis, Parsons, & Stirratt, 2001;Stall et al, 1986;Stall & Purcell, 2000;Waldo, McFarland, Katz, MacKellar, & Valleroy, 2000). However, drug use did not significantly mediate the effects of stress on unprotected anal intercourse.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with research that showed a causal link between illicit drug use and HIV-risk behavior in this population (Halkitis, Parsons, & Stirratt, 2001;Stall et al, 1986;Stall & Purcell, 2000;Waldo, McFarland, Katz, MacKellar, & Valleroy, 2000). However, drug use did not significantly mediate the effects of stress on unprotected anal intercourse.…”
Section: Discussionsupporting
confidence: 82%
“…While previous research has linked alcohol use with risky sexual behaviors (Stall, McKusick, Wiley, Coates, & Ostrow, 1986), only illicit drug use significantly predicted inconsistent condom use in the current study. This finding is consistent with research that showed a causal link between illicit drug use and HIV-risk behavior in this population (Halkitis, Parsons, & Stirratt, 2001;Stall et al, 1986;Stall & Purcell, 2000;Waldo, McFarland, Katz, MacKellar, & Valleroy, 2000).…”
Section: Discussioncontrasting
confidence: 49%
“…[4][5][6][7] Reducing alcohol use can therefore be seen as key to reducing HIV infection. [8][9][10] Yet this inevitably conflicts with SABMiller's underlying goal of maximizing profits from alcohol sales.…”
Section: Anna B Gilmore a And Gary Fooks Amentioning
confidence: 83%
“…Misuse of alcohol is related to risk taking, disinhibition and lack of self-care, and these types of behaviour are associated with the risk of contracting AIDS. Stall et al 12 found a strong relationship between the use of drugs and/or alcohol during sexual activity and noncompliance with safety techniques. AIDS prevention programmes need to take into account the complex relationships between alcohol and drug misuse and sexual activity.…”
mentioning
confidence: 99%